THE PLEISTOCENE CAVE LIFE OF BILLA SURGAM, KARNUL: A STUDY - Yalala, Shivanad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It is well known that the Billa Surgam caves of Karnul afford us sure proof of Palaeolithic cave-dwellers in India and eminent authorities would even characterize some of their artifacts as Magdalenian. Though the caves were discovered and partly explored in 1844 by Captain Newbold they were forgotten till more than forty years afterwards when their systematic exploration was undertaken, at the suggestion of Huxley, by Madras Government. There can be now little doubt that Karnul was one of the most ancient settlements of Palaeolithic man in India and many caves were found near Billa Surgam or within a few miles of it containing distinct traces of human habitation.